Characterisation of yeasts isolated from different local fruits and plant parts and their potential as probiotics - Noroul Asyikeen, Zulkifli; M. Abd Ghani, .; S. Abdul Mutalib, . (2020)
Thirteen (n = 13) yeast strains isolated from different local fruits and plant parts were characterised by polymerase chain reaction–restriction fragment length polymorphism analysis. By using four restriction endonucleases (AluI, Hae-III, Hind III and HinfI) on amplicon-Targetedinternal Transcribed Spacer 1 (ITS1) and ITS2 regions, all yeast strains (n =13) were found to be Saccharomycessensuscripto group with Hae III which was the best limiting enzyme to differentiate between S. cerevisiae/S. paradoxus (325, 230, 170 and 125 bp) and S. bayanus/S. postrianus (495, 230 and 125 bp). Based on 5.8s rRNA gene, six yeast strains were identified as Saccharomyces cerevisiae, three strains were identified as S. paradoxus, and two strains were identified as S. bayanus and S. postrianus each. Probiotic test was conducted on 13 yeast strains which were grown on bile salt with concentrations from 0.3 to 1%. All strains were also examined for bile deconjugation, lysozyme tolerance and ability to utilise prebiotics. All yeast strains grew in bile salt at 0.3% concentration. However, only S. cerevisiaevar WU-Y2 (SM16) survived in 1% concentration. In bile deconjugation test, all yeast strains demonstrated reduction in growth and low tolerance towards high concentration of lysozyme (100 ppm). The yeast strains also revealed low growth in inulin, xylitol and lactulose (2% v/w).